القيود الواردة على نظرية الإرادة وصعوبات تطبيقها على العقد الالكتروني (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research deals with the limitations of the parties' freedom to choose the law applicable to their electronic contract, which is known as the principle of the power of the will, then I explained whether the absolute will of the parties is not subject to any restriction or condition. Or are there restrictions imposed by ...?then I explained that the difficulties in applying the theory of will on the electronic contract, and explained that there are difficulties  related to the explicit selection of the law applicable to the electronic contract and other difficulties related to the implicit choice. I explained that the difficulties related to explicit selection can be divided into two categories concurrent with the selection process and another category of posterior choice.  تناول هذا البحث القيود الواردة على حرية الأطراف في اختيار القانون الواجب التطبيق على العقدالالكتروني, وهو ما يعرف بمبدأ سلطان الإرادة, وحاولت فيه الإجابة عن التساؤل المثار حول ما اذا كانت إرادة الأطراف مطلقة لا تخضع لأي قيد أو  شرط.... ؟ أم أن هناك قيوداً تحكمها...؟ ثمَّ شرحت الصعوبات الموجودة في تطبيق نظرية الإرادة على العقد الالكتروني, وأوضحت أن هناك صعوبات متعلقة بالاختيار الصريح للقانون الواجب التطبيق على العقد الالكتروني, وصعوبات أخرى تتعلق بالاختيار الضمني, وأوضحت إن الصعوبات المتعلقة بالاختيار الصريح يمكن تقسيمها إلى فئتين:  فئة  متزامنة مع عملية الاختيار وفئة أخرى لاحقة للاختيار.